ANALISIS KELAYAKAN USAHA BUDIDAYA RUMPUT LAUT DI DESA MALLASORO KECAMATAN BANGKALA KABUPATEN JENEPONTO - Irmayani Irmayani; Syarifuddin Yusuf; Muhammad Nispar (Program Studi Agrobisnis Perikanan, Fakultas Perikanan dan Ilmu Kelautan, UHO, 2014)
This study aimed to find out how much the income of farmers who cultivated seaweed Eucheuma sp cottonii, in the Village District of Bangkala Mallasoro Jeneponto, to determine whether seaweed farming developed in the Village District of Bangkala Mallasoro Jeneponto financially feasible to develop. This study was conducted in the District Mallasoro Jeneponto using a sample of 15 farmers seaweed taken by Simple Random Sampling with analysis techniques Revenue, Net Present Value, Return Rate Index. The results showed that the seaweed farmers income of Rp50.385.000, Net Present Value (NPV) of Rp20.573.720 and the Index Return Rate (IRR) of 47.67 % Seaweed Farming Village Mallasoro, District Bangkala Jeneponto feasible to be developed because it provides economic benefits.